Factors in successful GED recipients in higher education. - Pollard, Stan. (My University, 2006)
An inductive phenomenological study was conducted using eight GED recipients who had attempted higher education at a four-year university with this researcher's own experiences included. Four members of the study were successful in the completion of their desired degree. Each recipient was interviewed and their personal history analyzed for relevant themes. The analysis of these personal histories revealed themes within both groups and one substantial theme shared by both. The relevant themes that emerged within the successful group were: Career driven majors; Uninterrupted attendance, and Family support. Within the non-successful group the themes were: Women's struggle with multiple roles; Abusive relationships; and Two-year college enrollment. The shared theme was: Poor quality of instruction.

For over a half century the General Educational Development Test (GED) has been accepted as an equivalent to an earned high school diploma, which can then be used by the successful recipient to gain access into institutions of higher education. Research has shown that the majority of this population is seeking to advance their present status by working toward a degree in higher education. However, research has also shown that members of this population are at a greater risk than their traditional and non-traditional counterparts for not completing their educational goals.

Studies have been done over the years that tract the success/failure ratios of these students compared to traditional students, but these studies do not illuminate the differences between the successful and non-successful GED recipients who attempt higher education. The purpose of this research was to investigate these differences and see which, if any, were correctable impediments that could be used to help other GED recipients wishing to attempt higher education in the future.
Keywords: College dropouts.; Education, Higher.; GED tests; Academic achievement.; High school dropouts Education (Higher) United States.; Education, Adult and Continuing.